Biocompatible, Resilient, and Tough Nanocellulose Tunable Hydrogels - Amir Rudich; Sunaina Sapru; Oded Shoseyov (Nanomaterials, 2023)
Hydrogels have been proposed as potential candidates for many different applications. However, many hydrogels exhibit poor mechanical properties, which limit their applications. Recently, various cellulose-derived nanomaterials have emerged as attractive candidates for nanocomposite-reinforcing agents due to their biocompatibility, abundance, and ease of chemical modification. Due to abundant hydroxyl groups throughout the cellulose chain, the grafting of acryl monomers onto the cellulose backbone by employing oxidizers such as cerium(IV) ammonium nitrate ([NH4]2[Ce(NO3)6], CAN) has proven a versatile and effective method. Moreover, acrylic monomers such as acrylamide (AM) may also polymerize by radical methods. In this work, cerium-initiated graft polymerization was applied to cellulose-derived nanomaterials, namely cellulose nanocrystals (CNC) and cellulose nanofibrils (CNF), in a polyacrylamide (PAAM) matrix to fabricate hydrogels that display high resilience (~92%), high tensile strength (~0.5 MPa), and toughness (~1.9 MJ/m3). We propose that by introducing mixtures of differing ratios of CNC and CNF, the composite’s physical behavior can be fine-tuned across a wide range of mechanical and rheological properties. Moreover, the samples proved to be biocompatible when seeded with green fluorescent protein (GFP)-transfected mouse fibroblasts (3T3s), showing a significant increase in cell viability and proliferation compared to samples comprised of acrylamide alone.